Geological factors and mechanism of sinkhole development in Cho Don zinc-lead mining area, Bac Kan province, North of Vietnam - Van Hoang Nguyen; Quoc Cuong Tran; Kasatkin S. (Russian Journal of Earth Sciences)
The Cho Don district of Bac Kan province in North Vietnam is rich in minerals. The most common among them are iron, lead and zinc ores found in large reserves. The Na Tum mine in Cho Don district, Bac Kan province, became functional in April 2007. However, since December 2007, a number of large sinkhole formations have been reported. Dewatering of the Na Tum mine is considered to be the main factor behind sinkhole formation. However, there are certain other causative factors and conditions of sinkhole development and formation, which have been identified in this paper. A quantitative soil mechanic model has been applied for determining the sinkhole sizes along with the soil physical and strength parameters of the soil. Moreover, the process of sinkhole development is studied in detail in terms of suffusion and suffosion, the removal of soil particles from the massif with or without a change in volume, respectively. Different geometric criteria have been used and applied for the identification of the soil suffusion/suffosion vulnerability and have proven the reliability of the analysis applicability. The site-specific hydrological and hydrogeological conditions such as groundwater (GW) level regime which create suffusion/suffosion conditions for the formation of soil-caves above karstic formation have been identified. The soil resistance analysis using horizontal stress based on the soil arching theory has been carried out to determine the sliding potential of a particular soil cylinder above the underground soil cave. The results are essential for preventing sinkhole development in the study area, and the application of the methodology would be very useful for other sinkhole-vulnerability analyses under similar conditions.